Spatio-temporal evolution and influencing factors of rural production-living-ecological function: A case study of mountainous counties in Zhejiang Province, China - Xu, Zhiyuan; Ke, Fuyan; Yu, Jiajie (Frontiers in Environmental Science, 2025)
Production-living-ecological function (PLEF) represent the core dimensions of rural systems. However, systematic studies on PLEF in mountainous counties along China’s southeastern coast remain insufficient. Additionally, the dominant factors influencing rural functional evolution require deeper investigation, as these insights are crucial for regional sustainable development. This study focuses on mountainous rural areas in Zhejiang Province, a leading region in China’s rural revitalization. A PLEF evaluation index system was established. Using comprehensive evaluation methods, exploratory spatial data analysis (ESDA), and geographical detector (GeoDetector) models, we measured the PLEF development index of mountainous counties in Zhejiang Province from 2005 to 2020. Spatio-temporal evolution and spatial autocorrelation analyses were conducted, followed by identification of influencing factors. The results show that: (1) The average PLEF development index increased from 0.88 in 2005 to 1.56 in 2020, with growth contributions ranked as: living function (LF) > ecological function (EF) > production function (PF); (2) The developmental stages of PF, LF and EF transitioned from a “low-low-medium” pattern to a “medium-medium-high” configuration; (3) PLEF exhibited spatial agglomeration characteristics; however, the spatial agglomeration weakened and spatial dependency decreased during the study period; (4) Dominant factors shifted across subsystems: PF transitioned from agricultural production functions to non-agricultural production functions; LF shifted from life support functions to social welfare functions; EF remained primarily driven by ecological provisioning functions. These findings offer theoretical foundations for coordinating rural PLEF development and enhancing sustainability.